1999
DOI: 10.1093/emboj/18.9.2384
|View full text |Cite
|
Sign up to set email alerts
|

PDZ-mediated interactions retain the epithelial GABA transporter on the basolateral surface of polarized epithelial cells

Abstract: The PDZ target motifs located in the C-terminal end of many receptors and ion channels mediate protein-protein interactions by binding to specific PDZ-containing proteins. These interactions are involved in the localization of surface proteins on specialized membrane domains of neuronal and epithelial cells. However, the molecular mechanism responsible for this PDZ protein-dependent polarized localization is still unclear. This study first demonstrated that the epithelial γ-aminobutyric acid (GABA) transporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
130
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(138 citation statements)
references
References 41 publications
7
130
1
Order By: Relevance
“…5B). Following a 10-min incubation with IL-1␤, IL-1RII receptors were found to colocalize with internalized WGA-labeled surface glycoproteins, indicating the involvement of receptor-mediated endocytosis during internalization of IL-1␤ in these cells (30,31). At later time points (results not shown), similar colocalization was also observed occurring in some cells even in the absence of IL-1␤.…”
Section: Internalization Of Il-1rii In Different Cellular Contexts Anmentioning
confidence: 66%
See 1 more Smart Citation
“…5B). Following a 10-min incubation with IL-1␤, IL-1RII receptors were found to colocalize with internalized WGA-labeled surface glycoproteins, indicating the involvement of receptor-mediated endocytosis during internalization of IL-1␤ in these cells (30,31). At later time points (results not shown), similar colocalization was also observed occurring in some cells even in the absence of IL-1␤.…”
Section: Internalization Of Il-1rii In Different Cellular Contexts Anmentioning
confidence: 66%
“…This plant lectin glycoprotein is a marker of membrane transport (30) as it readily binds cell surface glycoproteins colocalizing with them upon endocytosis. Moreover, upon exposure of cells to IL-1, IL-1RII associates with the early endosome protein, EEA-1.…”
Section: Discussionmentioning
confidence: 99%
“…Movement of protein cargo along microtubules was shown to depend on the interaction of KIF17 with mLIN-10. Intriguingly, mLIN-2 binds mLIN-7 in epithelial cells where mLIN-7 acts to retain betaine-glutamate transporter 1 at the basolateral surface (10). Hence, protein complexes that include mLIN-2 seem to serve both dynamic and static functions.…”
mentioning
confidence: 99%
“…It is currently unknown how mLin-7C localizes at the nectin-based cell ± cell junctions, but the present results indicate that mLin-7C is associated with afadin or ZO-1 indirectly through an unknown molecule in an actin cytoskeleton-independent manner. mLin-7C forms a ternary complex with mLin-2 and mLin-10 (Borg et al, 1998;Butz et al, 1998) and each of these molecules interacts with many other molecules: mLin-7 with PSD-95, type 2 NMDA receptors, BGT-1, Pals, b-catenin, and VAM-1 (Jo et al, 1999;Perego et al, 1999Perego et al, , 2000Kamberov et al, 2000;Tseng et al, 2001); mLin-2 with neurexin, syndecan, protein 4.1, calcium channels, Tbr-1, hDlg, JAM, and rabphilin3A (Hata et al, 1996;Cohen et al, 1998;Hsueh et al, 1998Hsueh et al, , 2000Maximov et al, 1999;Nix et al, 2000;Martinez-Estrada et al, 2001;Zhang et al, 2001); and mLin-10 with amyloid precursor protein, Munc-18, neurexins, and KIF17 (Borg et al, 1996;Okamoto and SuÈ dhof, 1997;Biederer and SuÈ dhof, 2000;Setou et al, 2000). These earlier observations together with the present results suggest that these proteins directly or indirectly binding to mLin-7 are recruited to the nectinbased cell ± cell junctions.…”
Section: Discussionmentioning
confidence: 99%
“…mLin-7 interacts with mLin-2, which furthermore interacts with mLin-10, resulting in the formation of a heterotrimeric complex (Borg et al, 1998;Butz et al, 1998). Moreover, mLin-7 interacts with many other proteins, including PSD-95, type 2 NMDA receptors, BGT-1, Pals, b-catenin, and VAM-1 (Jo et al, 1999;Perego et al, 1999Perego et al, , 2000Kamberov et al, 2000;Tseng et al, 2001). We have previously shown that mLin-7 localizes at cell ± cell junctions including adherens junctions (AJs) in cultured Madin-Darby canine kidney (MDCK) cells, but it remains unknown how mLin-7 localizes at AJs (Irie et al, 1999).…”
mentioning
confidence: 99%